2021
DOI: 10.1186/s40738-021-00096-5
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of luteal phase progesterone support in true natural cycle cryopreserved blastocyst stage embryo transfers: a retrospective cohort study

Abstract: Background More than 67% of all embryos transferred in the United States involve frozen-thawed embryos. Progesterone supplementation is necessary in medicated cycles to luteinize the endometrium and prepare it for implantation, but little data is available to show if this is beneficial in true natural cycles. We evaluated the use of luteal phase progesterone supplementation for cryopreserved/warmed blastocyst transfers in true natural cycles not using an ovulatory trigger. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In 2013, a RCT with small sample size ( n = 102) conducted by Eftekhar et al comparing NC-FET with no LPS, LPS did not result in higher clinical pregnancy and implantation rates or lower miscarriage rates ( 9 ). Coincidentally, Waldman et al reported similar results in their retrospective study ( 10 ). Nevertheless, several recent studies showed that patients undergoing LPS with vaginal P 4 in NC-FET had higher LBR and lower miscarriage rates ( 11 13 ).…”
Section: Introductionsupporting
confidence: 52%
“…In 2013, a RCT with small sample size ( n = 102) conducted by Eftekhar et al comparing NC-FET with no LPS, LPS did not result in higher clinical pregnancy and implantation rates or lower miscarriage rates ( 9 ). Coincidentally, Waldman et al reported similar results in their retrospective study ( 10 ). Nevertheless, several recent studies showed that patients undergoing LPS with vaginal P 4 in NC-FET had higher LBR and lower miscarriage rates ( 11 13 ).…”
Section: Introductionsupporting
confidence: 52%
“…The application of luteal phase support (LPS) in true-NC FET remained to be elucidated. The available retrospective studies revealed that some studies suggested the application of LPS ( 41 ), whereas other studies showed comparable reproductive outcomes in true-NC FET with or without LPS ( 42 44 ). A RCT demonstrated that administration of progesterone (vaginal micronized progesterone 400 mg bid) from the day (LH surge+3 day) of true-NC FET (cleavage-stage embryos) had a higher LBR than no LPS ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…In t-NC, regarding the available retrospective studies some favor LPS (82) whereas others report comparable reproductive outcomes with or without LPS (67,83,84).…”
Section: Is Lps Needed In T-nc or Modified-nc?mentioning
confidence: 99%